On Innovation in the Plot of Epic Olonkho “Buura Dokhsun” - Filippov, Gavril Gavrilievich (Journal of History Culture and Art Research, 2018)
For the first time in olonkho studies, this article raises the question of innovation in the plot of the Yakut epic olonkho. Researcher of the plot of olonkho N.V. Emelyanov distinguishes three main types: plots of olonkho about settlement of the Middle world by the aiyy aymaga tribes; plots of olonkho about ancestors of the tribe; plots of olonkho about defenders of the tribe. The researcher considers the following criteria to distinguish plot types: 1. By the birth of the universe and the main heroes of olonkho; 2. By the destiny of the main heroes of olonkho; 3. By the general organization and construction of the olonkho characters system. Therefore, researcher views the plot of the Yakut olonkho as established and quite preserved mythologized oral heroic narrative about past social and political historical events of the pre-state Yakut people tribal system. Thus, new adding in the plot is considered possible, but it cannot drastically change the established ideological and informative tradition of the Yakut olonkho. Accordingly, the plot of olonkho that does not correspond to the described by N.V. Emelyanov traditional types of existing olonkho, either cannot be considered as true olonkho; or does not fit into existing scientific criteria for outlining plot types of olonkho; or there are new plot changes that do not correspond to traditional canons of olonkho. In this article, the plot of the olonkho “Buura Dokhsun” by author of olonkho S.S. Yakovlev – Erilik Eristiin is considered. While analyzing the plot of this olonkho, descriptive, componential, structural and comparative methods were used. In our opinion, the plot of the olonkho “Buura Dokhsun” of the author S.S. Yakovlev – Erilik Eristiin does not correspond to three plot types of the Yakut olonkho described by N.V. Emelyanov. We consider it to be new feature of the author, and, therefore, we think it is necessary to place it as a special problem in olonkho studies. New features in the plot of olonkho “Buura Dokhsun” are: the battle between Buura Dokhsun’s father and Yuryung Aar Aiyy Toyon for power and his sending to exile to the Middle World; rebellious appeals of Buura Dokhsun against lords of the Upper and Lower Worlds for their oppression; the violence of Buura Dokhsun over the lord of the Upper World Yurung Aar Aiyy Toyon and the release of all imprisoned people. These new features break traditional plots of the Yakut olonkho and represent the influence of the class conflict ideas of modern era.